PERANAN GURU SEJARAH DALAM MENINGKATKAN INDEKS PRESTASI SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI KELAS 2 MTs. DARUL FALAH SALO, KABUPATEN KAMPAR - Muallipa, Aini; ', H.Isjoni; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: From observation and experience in class 2 MTs. Darul Falah Salo, Kampar encountered in particular the impact the history lesson is of 21 students more than 50% (11 students) of them scored below a minimum completeness criteria (KKM) is set 75 schools on the subjects of history. Based on these results, the researchers are interested in knowing the appropriate actions to improve student achievement index to the school by using STAD type cooperative learning model in history lessons in class 2 MTs. Darul Falah Salo, Kabupaten Kampar.This classroom action research conducted in class 2 MTs. Darul Falah Salo, Kabupaten Kampar Academic Year 2016/2017 the number of students 21 people. This study was conducted in Mai 2016 to June 2016 consisting of two cycles.Based on the survey results revealed the activity of teachers in the first cycle with the clarification 23:00 Enough votes, while the second cycle increased with the clarification Very Good, it can be seen from the average score is 38.50 diproleh. Activities of students in the first cycle 128.5 (67.99%) with clarification, please vote. While on the second cycle increased by clarification of assessment is very good, it can be seen from the scores obtained by the average score between the first meeting and the second meeting of 173.5 (92.86%). The results of the first cycle study shows that classical learning outcomes are still low with an average of 65.47 or under KKM, while in the second cycle reached an average of 75.86 or rises above a predetermined KKM is 75.Key Words: Role, GPA, STAD